2017
DOI: 10.1186/s12966-017-0541-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, trajectories, and determinants of television viewing time in an ethnically diverse sample of young children from the UK

Abstract: BackgroundExcessive screen viewing in early childhood is associated with poor physical and psycho-social health and poor cognitive development. This study aimed to understand the prevalence, trajectory and determinants of television viewing time in early childhood to inform intervention development.MethodsIn this prospective longitudinal study, mothers of 1558 children (589 white British, 757 Pakistani heritage, 212 other ethnicities) completed questionnaires when their children were approximately 6, 12, 18, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
3
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 32 publications
(44 reference statements)
9
73
3
11
Order By: Relevance
“…This highlights that large studies with sufficient statistical power may be needed to identify relationships. Every 1 h/d was associated with only a 0.075‐cm larger waist circumference; however, considering this was a study of young children who are on a trajectory of increased daily TV viewing , and measurement error may have underestimated the magnitude of our reported associations, it is reasonable to consider that the results may still be clinically meaningful in the long term. Reviews have similarly deliberated that although associations with adiposity tend to be weak, nearly all children watch TV, and therefore a small “effect” across a very large population could be significant for public health .…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…This highlights that large studies with sufficient statistical power may be needed to identify relationships. Every 1 h/d was associated with only a 0.075‐cm larger waist circumference; however, considering this was a study of young children who are on a trajectory of increased daily TV viewing , and measurement error may have underestimated the magnitude of our reported associations, it is reasonable to consider that the results may still be clinically meaningful in the long term. Reviews have similarly deliberated that although associations with adiposity tend to be weak, nearly all children watch TV, and therefore a small “effect” across a very large population could be significant for public health .…”
Section: Discussionmentioning
confidence: 79%
“…Despite increased home ownership of multimedia devices, TV viewing on a TV set remains the dominant screen time behavior in early childhood . A recent study reported that UK children aged around 6 months watched nearly 1 hour of TV per day, and viewing time more than doubled to exceed 2 hours daily by 36 months of age . Similar levels of TV viewing have been documented in young children internationally .…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations